BILINGUAL BEAUTY PRODUCT TEXT ON SOCIAL MEDIA: TRANSLATION METHODS AND AFFECTING FACTORS (The Proceedings of English Language Teaching, Literature, and Translation (ELTLT), 2021)
Beauty trends have received more exposure recently because of social media and people quickly became more interested. A translator must have the skill and method to find the proper terms of the source language and equivalent with the context, purpose, and culture of the target language. This study is aimed to identify the translation methods applied in translating advertisement text about beauty product on social media. This study applied descriptive qualitative approach to describe translation method. There are three translation methods found in this study: communicative translation, free translation, and semantic translation. The methods are affected by the purpose, the readership, the text type, and the translator’s attitude.